Five-year carry-over effects in dune slack vegetation response to hydrology - Lisanne van Willegen; Hilary Wallace; Angela Curreli; Ciara Dwyer; John Ratcliffe; Davey L. Jones; Graham Williams; Martin Hollingham; Laurence Jones (Ecological Indicators)
Dune slacks are biodiverse seasonal wetlands within sand dune systems, strongly influenced by the dynamics of the local groundwater regime. Future climate predictions indicate strong adverse impact on the hydrology and therefore ecology of these wetland ecosystems. In this study we aimed to find the most appropriate hydrological and ecological indicators to summarise dune slack plant community responses to hydrology over multiple years. We evaluated 80 hydrological metrics (weighted and un-weighted median, mean, minimum, maximum, mean spring level, averaged over 1–8 year duration, and 5 additional 1-year metrics) against plant community responses (variants of Ellenberg EbF moisture indicator). The data were drawn from 453 relevées in 17 dune slacks, using permanent quadrats and co-located piezometers, set up in 2010 with vegetation monitoring repeated six times until 2019. Within our study we found a strong relationship between multiple hydrology metrics and the plant community response, but this displayed inter-annual variation with different patterns and correlations between years. The best performing hydrology metric was the unweighted 5-year average mean spring water level (MSL), linked to unweighted mean EbF using vascular plant species only. Maximum water level (MAX) also performed well, but MSL was preferred as MAX can be enhanced or truncated by topography leading to anomalies for individual slacks. MSL is also flexible to implement within manual monitoring programmes, which could be targeted to 3-months per year over the spring as a minimum requirement. These findings provide simpler metrics for site managers to monitor potential hydrology and vegetation responses to climate change.